Analisis Tegangan Mekanik Pada Mesin Press Hidrolik Dengan Beban 20 Ton - Sarjana, SS; Prawoto, Yogi; Umroh, Bobby; ., Rahmatullah; Idris, Muhammad (Rekayasa Material, Manufaktur dan Energi, 2023)
Hydraulic press machine is a tool used for work that requires a compressive action force. The stress distribution that occurs in this study will be determined in the development of a press machine under a state of pressing with a load of 20 tons. Researchers use Finite Element Analysis (FEA) to generate data on the stress circulation in the engine construction. The research objectives: (1) Calculate the hydraulic pressure strength in theory, (2) Calculate the mechanical stress in the hydraulic press construction manually using the ANSYS R15.0 software, (3) Calculate the strength of the hydraulic press construction manually and using the ANSYS R15 software. .0. In this review, FEA estimation is completed with the help of Ansys Workbench R15.0 programming. The information load comes from hydraulic pressure. The inspection strategy utilizes FEA with the type of underlying structural analysis. FEA simulation results stated, the maximum stress that occurs in the table is 98.646 MPa and the maximum deformation is 0.21613 mm. The results of Ansys analysis stated that the maximum stress that occurs on the table is 98.646 MPa and the maximum deformation is 0.21613 mm. Considering the Tresca hypothesis, it is found that the stresses and deformations that occur are below the standard for structural failure. So that the frame of the hydraulic press is safe for use in a load of 20 tons.